The prevalence of obesity and its associated factors among nursing students in Universiti Sains Malaysia - Zaini, Nur Zulfatul Izzah Mohammad (Universiti Sains Malaysia, 2023)
Obesity according to WHO (2021) is refers to Body Mass Index (BMI) greater than or equal to 30 kg/m². Obese people are at risk for many negative effects relating to health. Obesity has grown to epidemic proportions, with over 4 million people dying each year as a result of being obese in 2017, that caused a chronic health condition. This study aims to assess the prevalence of obesity, its association with physical activity, stress, eating behavior and selected socio-demographic factors among nursing students in USM. A cross-sectional survey was done using a set of self-administered questionnaires that contained questions from the IPAQ, PSS-10 and Eating Behavior scales. A total of 207 nursing students from Diploma and Bachelor programmes participated in this study. Data were analyzed by using SPSS version 27.0. The findings indicated that a total 24 (11.6%) nursing students had obesity. Most of the participants had moderate physical activity (45.4%), moderate stress (82.6%) and good eating behavior (20.7%). There is no significant association between obesity with physical activity (p=0.987), stress (p=0.970) and eating behavior (p=0.665). In terms of socio-demographic factors, a significant association was only indicated in age (p=0.048) and gender (p=0.048). In conclusion, although the prevalence of obesity is considered lower among nursing students in USM, appropriate and continuous initiative need to be done by the authorities to raise young people’s awareness on the bad impact of obesity and encourage them to keep practicing healthy life style.